2022
DOI: 10.1186/s13756-022-01181-0
|View full text |Cite
|
Sign up to set email alerts
|

The potential for the double risk of rabies and antimicrobial resistance in a high rabies endemic setting: detection of antibiotic resistance in bacterial isolates from infected dog bite wounds in Uganda

Abstract: Background Post-exposure treatment for dog bites in humans aims at alleviating the risk of rabies and promoting wound healing. Wound healing may be complicated by bacteria. This study identified the different bacteria and their antibiotic susceptibilities in infected dog bite wounds (DBWs) in Uganda. Methods A cross-sectional study was conducted among 376 dog bite patients. Wound swabs from patients with infected DBWs were collected and inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Dogs' oral cavities may harbor bacteria that can contaminate bite wounds and potentially spread to humans through licking (Kisaka et al, 2022;Tóth et al, 2022). Previous research has identified drug-resistant micro-organisms of public health significance in both people and companion animals (Kaspar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs' oral cavities may harbor bacteria that can contaminate bite wounds and potentially spread to humans through licking (Kisaka et al, 2022;Tóth et al, 2022). Previous research has identified drug-resistant micro-organisms of public health significance in both people and companion animals (Kaspar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%